Characterization of the microbial communities and their correlations with chemical profiles in assorted vegetable Sichuan pickles. (July 2020) - Rao, Yu; Qian, Yang; Tao, Yufei; She, Xiao; Li, Yalin; Chen, Xing; Guo, Shuyu; Xiang, Wenliang; Liu, Lei; Du, Hengjun; Xiao, Hang
Abstract: The Sichuan pickles of chili peppers, cowpeas and radishes were separately fermented for 12 days in order to identify the distinct microfloras and their correlations with the metabolites in different products. The chili pickle presented a slow fermentation process, high bacterial diversity within six phyla, and sixteen marker genera. Moreover, free amino acids accumulated in chili pickle and its main volatiles were alcohols and esters. Fast acidification and limited bacterial diversity within three phyla were found in Sichuan cowpea and radish pickles. The cowpea pickle was characterized by Lactobacillus and Pediococcus, as well as alcohols and alkenes. The radish pickle featured Lactococcus and Fructobacillus, as well as sulfides and aldehydes. Correlation analysis indicated that the metabolites, especially volatiles, were closely associated with not only the dominant bacteria but also those in low abundance. Highlights: The marker bacteria and characteristic metabolites in different Sichuan pickles were ascertained. The correlations between bacterial communities and chemical profiles were analyzed. Low abundance bacterial genera were significantly correlated to the metabolites, especially volatile organic compounds.